Aviation safety management systems. Issue 2 (1st January 2014) - Yeun, Richard; Bates, Paul; Murray, Patrick
The importance of a safety management system (SMS) is reinforced by the International Civil Aviation Organisation (ICAO)'s 2009 mandate requiring its introduction. The post SMS implementation findings of an ICAO council member state highlighted the need for a timely and verifiable project management structure when instituting such change. The appropriateness of using accident rates, number of accidents or audit results to measure of SMS effectiveness is discussed along with a comparison of some ICAO council member states' SMS frameworks.